Clinical Evaluation of Small Diameter Straumann Implants in Partially Edentulous Patients: A 5-Year Retrospective Study - M.Yaltirik; GÖKÇEN-RÖHLIG; S. OZER; G. EVLIOGLU (Tehran University of Medical Sciences, 2011)
Objective: The aim of the present study was to retrospectively evaluate small-diameter (3.3 mm) Straumann® dental implants placed in the maxilla or the mandible over a period of 5 years in function. Materials and Methods: Twenty- eight partially edentulous patients received a total of 48 implants over a 5-year period. After the standard healing period (3 to 6 months), the implants were restored with single-tooth prostheses or fixed partial dentures. All patients were followed according to a strict maintenance program with regular recalls. The cumulative survival rates of implants were analyzed and prosthetic complications were assessed. Results: After 5 years of function, one single 10-mm-long implant in the maxillary premolar region was lost because of recurrent peri-implant infection in a female patient. Two single 10-mm-long maxillary implants placed in the posterior region were lost due to body fracture. The cumulative 5-year survival rate of the implants was 93.75 %. The most common prosthetic complication was loosening of the occlusal screw. Conclusion: Within the limited observation period and the number of patients included in this study, it may be concluded that the use of small-diameter implants appears to be predictable if clinical guidelines are followed and appropriate prosthetic restorations are provided. However, it should be noted that fatigue fracture may occur.